HUBUNGAN ANTARA PENDIDIKAN, UMUR DAN PARITAS IBU DENGAN PEMILIHAN ALAT KONTRASEPSI AKDR DI PUSKESMAS PEMBINA PALEMBANG TAHUN 2010 – 2011 - Marchatus Soleha (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2015)
Family planning is one of the most basic preventive health services for women and primary. Declining birth rate have anything to do with the success of the national family planning. Based on data from the Health Center Trustees Palembang, the number of participants who use an IUD KB in the year 2010 - 2011 is (9.6%). The factors that affect fewer people using the IUD, among others, the factors age, knowledge, education, parity. The purpose of this study is to note the low selection of IUD contraception and Relationship Between Education, Age and Parity Mothers with IUD Contraception Election of Trustees at the health center Palembang Year 2010 to 2011. This research is a quantitative descriptive approach